ELECTRICITY GENERATION USING THERMOELECTRIC SYSTEM FROM WASTE HEAT OF FUEL GASES - Kumar, Pankaj; Pandey, Abhimanyau Pratap; Yadav, Praveen Kumar; Yadav, Sumit Kumar (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
Energy related cost have become a significant fraction of cost in any industry. The three top operating expenses are often to be found in any industry like energy (both electrical and thermal), labor and materials. If we were found the manageability of the above equipment’s the energy emerges a top ranker. So energy is best field in any industry for the reduction of cost and increasing the saving opportunity. Thermoelectric methods imposed on the application of the thermocouple particular in the industry for the recovery of waste heat. Finally the main attention is too focused on selecting the thermoelectric system and representing the analytical and theoretical calculation to represent the Thermoelectric System.